Mutant Rice Plant (Oryza sativa L.) Characteristic of M4 Generation from MSP13 with Higher Potential and Early Age - Zainudin, Agus; Ikhwan, Ali; Rahmawati, Revilda Ayu (Universitas Muhammadiyah Malang, 2023)
The aim of this study was to obtain information about plant characteristics from the result of M4 generation from MSP13 rice mutants which has the potential to have higher production yields and early maturity than non-mutant rice, Ciherang and Inpari 32. The research was conducted from April to August 2022. The location of this research was done in the Pendem area of Campus III, University of Muhammadiyah Malang, Tegalgondo village, Karangploso, Malang. The result of the research on the characteristic of M4 generation rice mutants (Oryza sativa L.) which has the potential to have higher production yields and early maturity indicated that M4 mutant rice plants aged 98.00 days on average is very early maturing, non-mutant is in the early maturing category with an average harvest age of 97.66 days, meanwhile Ciherang is in the early maturing category with an average harvest age of 99.33 days and Inpari 32 has an average of 99.33 days so it is included in the early maturing category. Rice age at flowering, plant height, rice age at harvest, number of productive tillers, panicle length, number of grains in each panicle, weight of 100 grains of M4 mutant rice plants differed with each comparison variation. Cluster analysis results for each variety with the variables age of rice at flowering, plant height, age of rice at harvest, number of productive tillers, length of panicles, total number of grain per panicle, total grain weight per panicle, number of full grain per panicle, grain weight fruitful per panicle, and 100 grain weight consisting of 2 groups. The first group has a similarity level of 30,80% while the second group has a similarity level of 30,77% with a kinship of K1 and K2 of 0.00%.